Decision Support System Implementation of Decision Tree Algorithm C4.5 In Employee Performance Assessment - Pasaribu, Afifah Balqis; Dedi Irawan, Muhammad (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
Employee performance assessment can be used as an evaluation tool to improve employee performance to achieve more. Some of the benefits of performance appraisal are such as improving business quality, driving business progress, and improving employee welfare. Yasmin Medical Clinic requires an employee performance appraisal system that can help superiors to process data properly so that it can shorten the time and produce an assessment that is in accordance with the subjective value of decision making. One method that can be used in a decision support system is a decision tree. Current decision trees such as C4.5 and CART are widely used in various fields. The results of the analysis show that the application of the decision support system of the decision tree algorithm c4.5 in employee performance appraisal is able to solve problems at the Yasmin Medical Clinic. A computerized decision support system helps the decision-making process and produces objective decisions that are in accordance with actual conditions.